Ulama Sebagai Legitimator Informasi Keuangan Masyarakat Perdesaan Di Era Digital - Ira Mirawati; Dadang Sugiana (Universitas Muhammadiyah Sidoarjo, 2018)
At the end of 2016, Muslim religious leaders are under the spotlight in relation to the success of 411 and 212 action calls that demand a judgment on Basuki Cahaya Purnama. This event shows that in this era of digital media, Muslim religious leaders still have an influence to mobilize the masses. Therefore, scholars need to be considered to participate to successing the development programs and become agents of change in the diffusion of innovation. Rural communities need ulama as opinion leaders or information legitimators, especially in the era of digital media that is developing today. Ulama is important to increase knowledge of rural communities including the field of finance and banking.Our Public Service Programme performed in Desa Cikondang, Kecamatan Cibeber, Kabupaten Cianjur Jawa Barat. In this location there are financial problems in the form of